Pineal Epidermoid Tumors: Report of Five Cases - ÖZEK, ERDİNÇ; Dinc, Cem; Iplikcioglu, Ahmet Celal; Ozek, ERDİNÇ (My University, 2013)
AIM: The aim of this study was to retrospectively analyse the clinical, radiological features and surgical outcome of pineal epidermoid tumors treated at a single neurosurgical department.